(untitled) (Research, Society and Development, 2021)
Colla corii asini or donkey-hide gelatin or ejiao is a gelatin obtained from the collagen of donkeys’ skin, used for thousands of years for various purposes in traditional Chinese medicine. Demand for ejiao, mixed with herbs and other ingredients in Chinese medicine, has increased due to the economic rise of the Chinese population in general. The donkey skins from countries like Kyrgyzstan, Brazil and Mexico go to China to produce Ejiao. In this extractive chain, Africa is the most affected territory, both in the number of animals slaughtered and in the social and economic impact. This work is a prospective patent survey on innovations and discoveries in the therapeutic use of ejiao. The research was carried out on three patent bases and from these the total of 1837 documents on technologies that make use of ejiao were recovered. Analyzing the temporal trajectory of publications in the area, it is observed that inventions started in the 90s and reached their peak in 2015, however there was a relapse in the following years, the assumption is that the decline was caused by the population reduction of donkeys in China and in the supplier countries of other regions of the world, in addition to the non-existence of the donkey skin production chain.